Pengaruh Phubbing At Workplace Dan Emotional Intelligence Terhadap Social Interaction Pada Kantor Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Mamuju Sulawesi Barat - Aisyah, Putri; Aqil, Muhammad; Halim, Agus; Ramli S, Ramli S; Suharlina, Suharlina (Pascasarjana Universitas Muhammadiyah Mamuju, 2025)
This study aims to confirm the influence between the variables phubbing at workplace, and emotional intelligence on social interaction. This study uses a quantitative method with data collection using a questionnaire. This study was conducted at the Office of Investment and One-Stop Integrated Services, Mamuju Regency, West Sulawesi. The sample used was all employees at the Office of Investment and One-Stop Integrated Services, Mamuju Regency, West Sulawesi, as many as 50 people, both ASN and non-ASN. The data obtained will be analyzed using SPSS with six tests including: validity test, reliability test, multiple linear regression test, partial test, simultaneous test, and coefficient of determination test (R2). The results of the study showed that partially phubbing at workplace had a significant effect on social interaction and emotional intelligence had an insignificant effect on social interaction. Simultaneously, phubbing at workplace and emotional intelligence had a significant effect on social interaction with a contribution of 16.4%, while 83.6% was influenced by other variables not examined in this study